Extratos aquosos da fungicultura no manejo de doenças em pimentão - Monteiro, Robson Eduardo Pereira (2024)
Peppers (Capsicum annum L.) are a crop of great economic, social and environmental importance, which has nutraceutical functionality, with worldwide production exceeding 36 million tons. However, its cultivation and production can be severely affected by diseases such as anthracnose (Colletotrichum spp.) and fusariosis (Fusarium spp.) which can make harvesting and marketing unfeasible. Alternative treatments to fungicides, such as fungiculture extracts (mushrooms and their post-cultivation substrate), have demonstrated efficiency in controlling fungi and protecting plants. Therefore, the objective of the work was to evaluate the efficiency of extracts from the mushrooms Pleurotus ostreatus, Lentinula edodes, Ganoderma lucidum and their respective spent substrates, in the management of Colletotrichum sp. and Fusarium sp., as well as its influence on the activity of enzymes linked to the induction of resistance in pepper plants and fruits. The experiment was carried out in the Phytopathology Laboratory and in a greenhouse, belonging to the Agricultural Sciences Center, at the Federal University of Paraíba. Isolates of Colletotrichum sp. and Fusarium sp. were obtained from symptomatic lesions of pepper plants and fruits. The treatments used were aqueous extracts of the mushrooms P. ostreatus (CPO), L. edodes (CLE), G. lucidum (CGL), spent substrate of P. ostreatus (SPO), L. edodes (SLE) and G. lucidum (SGL), substrate without mushroom cultivation, all at a concentration of 10% (100 mL L-1 of water), fungicide and control (sterilized distilled water). In the in vitro test, treatments were diluted in PDA culture medium, in Petri dishes and on top of it, a disk of pure colonies of both Colletotrichum sp. (chapter II) and Fusarium sp. (chapter III). Mycelial growth, percentage of colony inhibition, growth speed index, sporulation and percentage of sporulation inhibition were determined. The fruits were treated by immersion for 5 minutes, with four repetitions of two fruits per treatment. After 24 h, they were inoculated with a suspension of Colletotrichum sp. and on the 14th day, disease severity assessments were carried out with quantification of the injured area by image analysis, with the aid of ImageJ software. For post-harvest analyses, the treated fruits were distributed into four storage periods, with three replications of two fruits per treatment. Physicochemical analyzes of mass loss, firmness, pH, soluble solids, titratable acidity, SS/AT ratio and vitamin C were carried out. In the in vivo test, the seeds were treated and inoculated through direct contact with the Fusarium mycelium sp. and sown in pots containing commercial substrate. Plant height, stem diameter, root volume, root and shoot dry mass and infection rate were analyzed. At the end of the experiments, parts of the fruits and leaves from each replication were collected and the enzymatic activity of peroxidase, phenylalanine ammonia lyase and polyphenol oxidase was determined. Fungiculture extracts had influences on Colletotrichum sp. and Fusarium sp., in which they reduced their mycelial growth and sporulation, as well as maintaining the quality of the plants and post-harvest of Capsicum annuuum fruits. Pleurotus ostreatus mushroom extract reduced mycelial growth of both Colletotrichum sp. as well as Fusarium sp., the extract of the Lentinula edodes mushroom and its post-cultivation substrate promotes greater protection, both in fruits and pepper plants. All extracts tested induce the production of the enzymes peroxidase, phenylalanine ammonia-lyase and polyphenoloxidase involved in inducing resistance in plants in pathogen management.